Missão e Igreja local: um estudo do Vodu haitiano no contexto do pluralismo religioso - Joseph, Jean Anel (2015)
The mission received from Jesus Christ (cf. Mt 29, 19-20) has been accepted by the universal church, and is effective in the activity and outreach of each particular church. Therefore, we understand that a church becomes particular when it can take local cultural elements and incorporate them in the enculturation of the Gospel in this local reality. Indeed, the mission of making Jesus Christ known to the ends of the earth experiences many challenges regarding the languages, mentalities, political environments and cultures. It is in the process the enculturation, that Jesus Christ may be incarnated in a mission to liberate and to save the humanity. However, the process of evangelization is not always free of evangelizers cultures conceptions and, almost always the native people s cultures were fought, ignored, or repressed. This research studies the Haitian reality in the cultural shock between the process of Christian evangelization and voodoo. We try to contextualize both voices of the local church as their own writings on the international scene and also the vast theological thought of that time. We show also the work of the black leaders to insure recognition of the black culture, defending it against all prejudices, charges of fetishism, witchcraft and other issues combated the black culture where the voodoo is a form of expression. After analyzing the way the local church related to voodoo and the inspiration of the second Vatican Council, we search for pointing out possible alternatives that can lead a harmony between the two religions that are currently under the law, with the same degree of importance. We do not ignore the presence of other religions, but we place our focus on studying the pastoral elements that may make for a possible way to overcome the current challenges. This is demanded in the new plural context Haitian reality, especially since the legal recognition of Voodoo as a Religion and the arrival of new religions with the UN mission in Haiti since 2004. The conclusion underlines the hypothesis that A return to preconciliar practices can only hinder the activity of the local church if it wants to be in tune with the universal mission of the church and especially if it intends to respond to the appeal of the Continental Magisterial, and more specifically to the Aparecida Conference that calls for a pastoral conversion as required in response to the signs of the times